Switchability and minimal effect of food on pharmacokinetics of modified release tablet strengths of omecamtiv mecarbil, a cardiac myosin activator. (18th June 2021) - Trivedi, Ashit; Oberoi, Rajneet K.; Mackowski, Mia; Jafarinasabian, Pegah; Zhang, Hanze; Flach, Stephen; Simiens, Mary Ann; Terminello, Bianca; Abbasi, Siddique; Dutta, Sandeep; Lee, Edward
Abstract: Omecamtiv mecarbil (OM) is a cardiac myosin activator in clinical development for the treatment of heart failure. The effect of food on the pharmacokinetics (PK) of 25, 37.5, and 50 mg strength modified release (MR) tablets and the bioequivalence of two 25 mg tablets versus one 50 mg MR tablet were evaluated in two open‐label, randomized, cross‐over studies in healthy subjects. Subjects received two 25 mg tablets or one 50 mg OM MR tablet under fed or fasted states in Study 1 ( n = 39), and single oral doses of 25 and 37.5 mg OM MR tablets and to assess its relative bioavailability to the 25 mg MR tablet, a 25 mg oral solution under fed or fasted states in Study 2 ( n = 34). The area under the concentration–time curve (AUC) and the maximum observed concentration (Cmax ) of 25, 37.5, or 50 mg OM MR tablets were approximately 13%–22% higher and 31%–40% higher, respectively, when taken with food. The two 25 mg and one 50 mg OM MR tablets were bioequivalent (90% confidence intervals) of the geometric mean ratios for Cmax and AUC of OM were within 0.8–1.25 under the fasted or fed state. OM was well tolerated and all treatment‐emergent events were mild in severity and resolved by the end of the study. In conclusion, these studies demonstrated that the effect of food on the PK of OM was minimal at all three studied strengths of the MR tablets, and two 25 mg MR tablets may be switched for one 50 mg MR tablet (EudraCT Number: 2019‐003683‐44). Abstract : The clinical studies demonstrated that the effect of food on omecamtiv mecarbil pharmacokinetics was minimal at all three studied strengths (25, 37.5 or 50 mg) of the modified release tablets. The study also supports that two 25 mg modified release tablets may be switched for one 50 mg modified release tablet.